Behavioral Barriers to Digital Health and Conditions of Digital Resilience Among Older Adults: Evidence from China - Yu Ren; Weihua Yang; Wan Li (Behavioral Sciences, 2026)
As health services shift to digital delivery, older adults face practical online risks, including operational errors, difficulty interpreting clinical information, unclear privacy consent procedures, and telecommunications fraud. Existing empirical work mostly adopts questionnaire and interview designs to document older adults’ real-world digital usage, yet few studies systematically analyze policy documents as an external intervention system and assess how they address four core usage barriers: limited digital proficiency, constrained service access, weak sustained participation, and individualized online safety threats. This paper analyzes 1008 policy records extracted from the Peking University Legal Database covering 2007–2025, and develops a four-dimensional analytical framework split into B1 (Digital Capacity and Age-Friendly Support), B2 (Digital Health Management Support), B3 (Home- and Community-Based Care Support), and B4 (Institutional Care and Risk Governance). The analytical toolkit combines a Capability–Opportunity–Motivation–Behavior (COM-B) diagnostic model, an M1–M4 intervention-mechanism coding protocol, Latent Dirichlet Allocation (LDA) topic modeling, and two indices: the Digital Adaptation Policy Orientation Index (DAPOI) and the Behavioral Intervention Diversity Index (BIDI). Coding outputs reveal a pronounced structural imbalance in policy allocation for older adults’ digital health in China: community and institutional governance clauses (B3, B4) dominate the corpus, while person-centred support including one-on-one operational coaching, clinical data interpretation guidance and offline manual backup channels accounts for a marginal share of all coded entries (B1, B2). Age-friendly digital policies issued circa 2020 serve primarily short-term emergency adjustments instead of permanent institutional arrangements. Built on full-text policy coding outputs, this work defines policy-supported digital resilience as a holistic protective system formed by coordinated institutional clauses. Every result reported is sourced exclusively from supply-side policy records, which provides policy-level evidence for subsequent behavioral research on older adults’ digital risk management and digital welfare construction.